VOLATILE COMPOUNDS DURING THE RIPENING OF COLOMBIAN SOURSOP (Annona muricata L. cv. Elita) COMPUESTOS VOLÁTILES DE LA GUANÁBANA COLOMBIANA (Annona muricata L. cv. Elita) DURANTE SU MADURACIÓN - Carlos J MÁRQUEZ C (Universidad de Antioquia, 2011)
Fruits of soursop (Annona muricata L. cv. Elita) were evaluated at different ripening stages to determine the changes in their physicochemical characteristics: total soluble solid content, percentage of acidity, pH, and ripeness index. The change in volatile compounds were determined through Headspace-Solid Phase Microextraction and subsequent Gas Chromatography-Mass Spectrometry analyses. The volatile compounds were identified through the comparison of their chromatographic and spectral properties against the ones exhibited by reference substances. The sensorial quality factors showed values that changed according to the ripening stage. It was established that the ester levels, particularly those from C6, C4, and C8 saturated and unsaturated aliphatic acids, increased with ripening. C6 aliphatic compounds, such as (Z)-3-hexenol and (Z)-3-hexenal, were observed to be the major volatile constituents in the green stage. In contrast, methyl hexanoate and methyl (E)-2-hexenoate were the main volatile in ripe, overripe and half ripe fruits. The overripe stage was characterized by an increase in the ethyl acetate, methyl butanoate and ethyl butanoate levels, and the appearance of butanoic and hexanoic aliphatic acids. These facts could be used as an indicator of the beginning of the fermentation stage and the loss of fruit sensory quality. Los frutos de guanábana (Annona muricata L. cv. Elita) en diferentes estados de madurez se evaluaron para determinar las características fisico-químicas: sólidos solubles totales, porcentaje de acidez, pH e índice de madurez. Los cambios en la composición de los compuestos volátiles se determinaron mediante la técnica de Espacio de Cabeza-Microextracción en Fase Sólida y el posterior análisis por Cromatografía de gases acoplada a espectrometría de masas. Los compuestos volátiles se identificaron por comparación de sus propiedades cromatográficas y espectrales con sustancias de referencia. Los factores de calidad sensorial mostraron valores que variaron con el estado de madurez. Además, se estableció que la cantidad de ésteres, especialmente los provenientes de los ácidos C6, C4 y C8, saturados e insaturados, se incrementaron con la maduración. Los compuestos alifáticos C6, como el (Z)-3-hexenol y el (Z)-3-hexenal, fueron los volátiles mayoritarios en la fruta verde; en tanto que el hexanoato de metilo y el (E)-2-hexenoato de metilo, fueron los más abundantes en las frutas maduras, sobremaduras y de madurez intermedia. En la sobremaduración aumentó la concentración de acetato de etilo, butanoato de metilo y butanoato de etilo; y aparecieron los ácidos alifáticos butanoico y hexanoico, los cuales pueden ser indicadores del inicio de la etapa fermentativa y de la pérdida de la calidad sensorial de la fruta.